Les yeux sont faits pour voir & pour pleurer — La photographie entre Budapest, Prague & Berlin - Soulages, François (Verbum – Analecta Neolatina, 2010)
Press photographers and politicians show us suffering bodies whose event-like visibility make us forget the invisibility of every day life, for the reality of day-to-day life is difficult to notice. We can accept tragedy more easily if heroes participate in it. A life lived in a dictatorship is very long, even if it is short for a historian who deals with long time periods, and it is impossible to capture for a press photographer. This paper deals with the questions that photographers have to face: what is it that they have to capture to be able to uncover the essence of the system? What bodies do they need to photograph? Are they bodies at all?